2017
DOI: 10.5852/ejt.2017.285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics and biogeography of the Hemigalinae civets (Mammalia, Carnivora)

Abstract: D N A L i b r a r y o f L i f e , r e s e a r c h a r t i c l eurn:lsid:zoobank.org:pub:EB6AF6D6-36E7-4677-87E8-D72C42A273AF Abstract. Due to the difficulty in obtaining samples, the systematics of the Hemigalinae civets has not been fully resolved. The aim of this study was to clarify the relationships of the species and the intraspecific diversity within this subfamily, and to explore the environmental factors that might have affected its evolution. Using two mitochondrial and two nuclear markers, we confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Maximum likelihood and Bayesian inference analyses (Fig. S1) of the concatenated sequences of the 13 PCGs (11,313 bp) support the monophyly of Viverridae among feliforms, the monophyly of Paradoxurinae among viverrids, the clustering of Paradoxurinae and Hemigalinae, as found by Veron et al (2017), and the clustering of Genettinae with Viverrinae as proposed by Veron (2007) and Eizirik et al (2010). The monophyly of Viverridae was strongly supported in both the analyses, with a Bayesian Posterior Probability (bpP) of 1 and a bootstrap support (BS) of 100%.…”
Section: Resultsmentioning
confidence: 65%
“…Maximum likelihood and Bayesian inference analyses (Fig. S1) of the concatenated sequences of the 13 PCGs (11,313 bp) support the monophyly of Viverridae among feliforms, the monophyly of Paradoxurinae among viverrids, the clustering of Paradoxurinae and Hemigalinae, as found by Veron et al (2017), and the clustering of Genettinae with Viverrinae as proposed by Veron (2007) and Eizirik et al (2010). The monophyly of Viverridae was strongly supported in both the analyses, with a Bayesian Posterior Probability (bpP) of 1 and a bootstrap support (BS) of 100%.…”
Section: Resultsmentioning
confidence: 65%
“…A breeding programme was established in Vietnam, with animals confiscated from the illegal wildlife trade, and breeding this species has been successful since 1997 (Veron et al, 2004). Genetic studies suggested the existence of two or three lineages (Veron et al, 2004;Veron, Bonillo et al, 2017), although further genetic data should be gathered to confirm this. Once verified, and if the lineages are geographically separated, it may be possible to identify the origin of confiscated animals and define conservation units for this species.…”
Section: Owston's Civetmentioning
confidence: 99%
“… 2010 , Veron et al. 2015 , 2017 ). Since, there is a limited genetic data available on Asian palm civet ( P. hermaphrodites) from Indian sub-continent, the present study will contribute significantly to in-depth phylogenetic studies and proper assessment of conservation status of this species.…”
mentioning
confidence: 98%